OVERVIEW ABOUT PROJECT QUALITY MANAGEMENT - Catalin Drob (Studies and Scientific Researches: Economics Edition, 2013)
The purpose of this study is to emphasize the main aspects regarding project quality management. This study tries to present in the comparative manner, different approaches of the main guidelines, international standards and methodologies regarding project quality management (the PMBOK ® Guide elaborated by the Project Management Institute, the PRINCE method elaborated by the British Office of Government Commerce etc.). The PMBOK® Guide describes three elements (processes) of quality management: quality planning (plan quality management), quality assurance (perform quality assurance) and quality control (control quality). The PMBOK approach regarding project quality management is that quality management must lead to achieving and validating project requirements. According the PRINCE method the quality is one of the six variables involved in any project. The PRINCE approach regarding project quality management considers that strategy in this field must lead to achieving just the level of quality needed to achieve in the project and not to ensuring the best quality.